Implementation Of Weighted Aggregated Sum Product Assessment (Waspas) Method In Determining English Language Learning Levels At Vanka Speaking Course Sumbawa - Andini, Virna Febri; Julkarnain, M.; Yuliadi, Yuliadi (Brilliance: Research of Artificial Intelligence, 2024)
English is an international language that plays a crucial role in global communication. English is very influential in aspects of life, ranging from the work sector to the education sector. Vanka Speaking Course Sumbawa is one of the course institutions in Sumbawa Regency that accepts participants from various levels, namely elementary to junior high school, with multiple levels and six levels of learning. Currently, Vanka Speaking Course Sumbawa has seven tutors with 142 students divided into 13 regular classes (117 people) and 12 private classes (25 people). In a language course like this, determining the student's learning level is a critical initial stage. This allows teachers to design learning programs with suitable modules and materials to meet the needs of each student. The course party still needs help determining the initial stage and learning level that suits the student's abilities. This study aims to apply the Weighted Aggregated Sum Product Assessment (WASPAS) Method in determining the level of English learning by selecting alternatives based on specific criteria. The development method designs the system using Rapid Application Development (RAD), PHP programming language, Laravel framework, MySQL database, and Unified Modeling Language (UML). After being built and tested using black box testing, this application can be run properly and help Vanka Speaking Course Sumbawa make decisions related to determining the level of English learning. The results of this study can improve the accuracy of assessment in determining the level of English learning in students and ultimately further improve the quality of learning at the Vanka Speaking Course.